Clinical features and infection risks of Chinese children with different types of Gaucher disease - Gan, Chuan; Wu, Yuanyuan; Qin, Tao (Frontiers in Pediatrics, 2025)
BackgroundGaucher disease (GD) is a rare autosomal recessive disorder caused by mutations in the glucocerebrosidase1 (GBA1) gene. Reports on the clinical presentations of various types of GD in Chinese children are scarce, and there is limited research addressing co-occurrence of GD with bacterial (including tuberculosis), viral, or fungal, infections. Pediatric GD typically manifests with greater severity due to developmental vulnerability of organ systems and immature immunity, leading to heightened infection risks. Unlike non-GD children, those with GD exhibit multiorgan involvement (e.g., hepatosplenomegaly, cytopenias) that predisposes them to opportunistic infections. In this study, we describe the clinical features and infection risks associated with different types of GD in Chinese children.MethodsThis study was done in Children's hospital of Chongqing Medical University. Seventeen patients aged <18 years, diagnosed with GD from January 2008 to December 2019, were enrolled. Clinical symptoms, laboratory results, mutation genotypes, and imaging data were collected for analysis.ResultsOf the 17 patients, 9 were diagnosed with Type 2 GD, while 4 each had Type 1 and 3 GD. Median (interquartile range) age of onset was 7 (3.0–18.5) months. Approximately two-thirds of patients experienced malnutrition, and most exhibited hepatosplenomegaly and hematological abnormalities. Anemia was the most frequent hematological disorder, followed by thrombocytopenia, with almost half developing leukopenia. Liver function abnormalities were common, particularly in Type 2 GD, and characterized by elevated aspartate aminotransferase and glutamyl transpeptidase levels, prolonged prothrombin time, and decreased albumin. Patients with Type 2 GD had increased susceptibility to infections, with respiratory failure from severe infections a leading cause of death. Genome sequencing revealed a novel deletion mutation (c.787_c.788 delAA) in the GBA1 gene associated with Type 2 GD.ConclusionIn pediatric patients with Gaucher disease, Type 1 GD is associated with worse hematological impairment, while Type 2 GD involves significant hepatic insufficiency and heightened susceptibility to infections.